2018
DOI: 10.1037/law0000181
|View full text |Cite
|
Sign up to set email alerts
|

The impact of waiver to adult court on youths’ perceptions of procedural justice.

Abstract: The current study examined perceptions of fair treatment in a past court experience among a sample of incarcerated youth (n = 364). Perceptions were compared for youth whose cases were processed through the juvenile (n = 261) versus adult court (n = 103) systems. In general, youth who were adjudicated in adult court felt more justly treated by legal authorities than youth adjudicated in juvenile court. Specifically, youth in adult court rated judges as only marginally more just than youth in juvenile court, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Across these studies, interactions with legal actors generally focus on judges and the police, and there is limited research examining interactions with defense attorneys and views of procedural justice. Exceptions include research by Kaasa et al (2018), who examined perceptions of fairness of court experiences among a sample of incarcerated youth, including juveniles waived to the adult criminal justice system and youth retained in the juvenile justice system. The main difference in procedural justice perceptions was that waived youth rated their defense attorneys as significantly fairer in their treatment than youth whose cases were kept in juvenile court (Kaasa et al, 2018).…”
Section: Procedural Justice and Defense Attorneysmentioning
confidence: 99%
See 1 more Smart Citation
“…Across these studies, interactions with legal actors generally focus on judges and the police, and there is limited research examining interactions with defense attorneys and views of procedural justice. Exceptions include research by Kaasa et al (2018), who examined perceptions of fairness of court experiences among a sample of incarcerated youth, including juveniles waived to the adult criminal justice system and youth retained in the juvenile justice system. The main difference in procedural justice perceptions was that waived youth rated their defense attorneys as significantly fairer in their treatment than youth whose cases were kept in juvenile court (Kaasa et al, 2018).…”
Section: Procedural Justice and Defense Attorneysmentioning
confidence: 99%
“…Exceptions include research by Kaasa et al (2018), who examined perceptions of fairness of court experiences among a sample of incarcerated youth, including juveniles waived to the adult criminal justice system and youth retained in the juvenile justice system. The main difference in procedural justice perceptions was that waived youth rated their defense attorneys as significantly fairer in their treatment than youth whose cases were kept in juvenile court (Kaasa et al, 2018). In a recent study, Lee et al (2020) found that attorney satisfaction was related to willingness to accept a plea.…”
Section: Procedural Justice and Defense Attorneysmentioning
confidence: 99%